2009
DOI: 10.1007/s00425-009-1055-7
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of fern Pteris vittata glutaredoxin PvGrx5 in Arabidopsis thaliana increases plant tolerance to high temperature stress and reduces oxidative damage to proteins

Abstract: A glutaredoxin of the fern Pteris vittata PvGRX5 was previously implicated in arsenic tolerance. Because of possible involvements of glutaredoxins in metabolic adaptations to high temperature stress, transgenic Arabidopsis lines constitutively expressing PvGRX5 were evaluated for thermotolerance. Homozygous lines expressing PvGRX5 exhibited significantly greater tolerance to high temperature stress than the vector control and wild-type, based upon growth during stress and during recovery from stress, and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Glutaredoxins have emerged to be key regulators in stress responses and organ development in plants (33,51,52). In the present study, we characterized an Arabidopsis monothiol glutaredoxin, AtGRXS17, and demonstrated that AtGRXS17 is a critical component involved in ROS accumulation, auxin signaling, and temperature-dependent postembryonic growth in plants.…”
Section: Discussionmentioning
confidence: 65%
“…Glutaredoxins have emerged to be key regulators in stress responses and organ development in plants (33,51,52). In the present study, we characterized an Arabidopsis monothiol glutaredoxin, AtGRXS17, and demonstrated that AtGRXS17 is a critical component involved in ROS accumulation, auxin signaling, and temperature-dependent postembryonic growth in plants.…”
Section: Discussionmentioning
confidence: 65%
“…Concerning class I GRXs, an Arabidopsis mutant deficient in both GRXC1 and C2 has a lethal phenotype because of impaired embryo development (Riondet et al, 2012). Among the four class II GRXs (S14, S15, S16, and S17), the plastidial S14 isoform participates in arsenic tolerance in a hyperaccumulating fern (Pteris vittata; Sundaram et al, 2008) and is induced in response to high temperature in Arabidopsis (Sundaram and Rathinasabapathi, 2010). Tomato (Solanum lycopersicum) plants silenced for the expression of GRXS16 encoding another plastid-localized GRX display increased sensitivity to osmotic stress (Guo et al, 2010).…”
mentioning
confidence: 99%
“…While transient expression of transgenic constructs does enable research, there is no substitute for stable transformation in functional genomics and plant biology. Researchers have resorted to studying fern gene function using heterologous expression in the angiosperm model plant Arabidopsis (Arabidopsis thaliana; Dhankher et al, 2006;Sundaram et al, 2009;Sundaram and Rathinasabapathi, 2010), which is far from optimal. Overexpression and knockdown analysis of individual genes in a wide variety of fern species would undoubtedly accelerate our ability to learn more about their biology and subsequently develop novel products from ferns.…”
mentioning
confidence: 99%